PENGARUH LAMA PENYIMPANAN SELAMA DISTRIBUSI DAN PEMASARAN TERHADAP VIABILITAS BAKTERI ASAM LAKTAT DAN TINGKAT KEASAMAN PADA YOGURT MURBEI HITAM (Morus nigra L.) - Oktavia, Hana Meliana; Kusumawati, Netty; Kuswardhani, Indah (Widya Mandala Surabaya Catholic University, 2015)
Yoghurt is the product from coagulation of milk that is produced from fermentation process of lactic acid bacteria (LAB), Lactobacillus bulgaricus (LB) and Streptococcus thermophilus (ST). Usually during storage and distribution, the viability of LB and ST decrease. Marketing and distribution method which is done by small scale industry is using combination storage on coolbox with 15oC-20oC during 10 hours and followed by storage on refrigerator with 5oC during 14 hours. The purpose of the research observe the effect of storage time on such condition. The research purposed to observe the effect of storage time during distribution and marketing on the viability of Lactic Acid Bacteria (ST and LB) and acidity levels in black mulberry yogurt. The research based on RBD (Randomized Block Design) single factor: the long of storage during distribution and marketing (1; 5; 9; 13; 17 and 21 days) with 4 replications. The parameters observed were pH, total acid and viability LAB (ST and LB). The data obtained were analyzed statistically with Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) (Î± = 0.05). The long of storage during distribution and marketing gave significant affect on the viability of lactic acid bacteria and the acidity of the black mulberry yogurt. The longer of storage time, the lower LAB viability and pH, but higher total acid. The value of black mulberry yoghurt ALT LAB after 21 days of storage 9.1484 log cfu / ml with a pH value of yogurt 3.814, acidity Soxhlet Henkel 95.03 oSH and total of lactic 2.14%. Black mulberry yogurt during 13 days of storage and distribution is qualified to SNI with 9.5148 ALT log cfu/mL and a total of lactid acid 1.97%.